Dasar Pemikiran Kerahasiaan Identitas Korban Tindak Pidana Kesusilaan - Leona Citra Maranatha; Ade Adhari (LPPM Universitas Ekasakti Padang, 2024)
Cases of criminal acts of morality continue to occur in Indonesia coupled with legal protection of the confidentiality of the victim's identity that has not been fulfilled. Of the many victims who experience sexual violence, these victims will experience serious physical and mental trauma due to what has been experienced and the things that then happen afterwards. This research aims to explore the reasoning for the confidentiality of the victim's identity. By using normative-empirical research, this study found that the reason for the confidentiality of the victim's identity is due to several things, namely: Pancasila, social reaction and legislation.